Prospective memory and frontal lobe function. Issue 2 (3rd March 2016) - Neulinger, Kerryn; Oram, Joanne; Tinson, Helen; O'Gorman, John; Shum, David H.K.
Abstract: The study sought to examine the role of frontal lobe functioning in focal prospective memory (PM) performance and its relation to PM deficit in older adults. PM and working memory (WM) differences were studied in younger aged ( n = 21), older aged ( n = 20), and frontal injury ( n = 14) groups. An event-based focal PM task was employed and three measures of WM were administered. The younger aged group differed from the other two groups in showing significantly higher scores on PM and on one of the WM measures, but there were no differences at a statistically significant level between the older aged group and the frontal injury groups on any of the memory measures. There were, however, some differences in correlations with a WM measure between groups. It is concluded that there are similarities and differences in the deficits in PM between older adults and patients with frontal lobe injury on focal as well as nonfocal PM tasks.